Impact of COVID-19 on diagnosis and management of paediatric inflammatory bowel disease during lockdown: a UK nationwide study. Issue 12 (30th July 2020) - Ashton, James John; Kammermeier, Jochen; Spray, Christine; Russell, Richard K; Hansen, Richard; Howarth, Lucy J; Torrente, Franco; Deb, Protima; Renji, Elizabeth; Muhammed, Rafeeq; Paul, Thankam; Kiparissi, Fevronia; et al.
Abstract : Background: COVID-19 has impacted on healthcare provision. Anecdotally, investigations for children with inflammatory bowel disease (IBD) have been restricted, resulting in diagnosis with no histological confirmation and potential secondary morbidity. In this study, we detail practice across the UK to assess impact on services and document the impact of the pandemic. Methods: For the month of April 2020, 20 tertiary paediatric IBD centres were invited to contribute data detailing: (1) diagnosis/management of suspected new patients with IBD; (2) facilities available; (3) ongoing management of IBD; and (4) direct impact of COVID-19 on patients with IBD. Results: All centres contributed. Two centres retained routine endoscopy, with three unable to perform even urgent IBD endoscopy. 122 patients were diagnosed with IBD, and 53.3% (n=65) were presumed diagnoses and had not undergone endoscopy with histological confirmation. The most common induction was exclusive enteral nutrition (44.6%). No patients with a presumed rather than confirmed diagnosis were started on anti-tumour necrosis factor (TNF) therapy. Most IBD follow-up appointments were able to occur using phone/webcam or face to face. No biologics/immunomodulators were stopped. All centres were able to continue IBD surgery if required, with 14 procedures occurring across seven centres. Conclusions: Diagnostic IBD practice has been hugely impacted by COVID-19, with >50% of new diagnoses not having endoscopy. To date, therapy and review of known paediatric patients with IBD has continued. Planning and resourcing for recovery is crucial to minimise continued secondary morbidity.